UMKM Naik Kelas: Mengkonstruksi Sebuah Desain Faktor Determinant Berluaran Perkembangan Usaha (Studi pada UMKM di Kota Semarang) - Sijabat, Rauly (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2020)
UMKM is recognized as having an important role as an economic buffer through its contribution to national GDP and unemployment reduction. However, the acknowledgment, the reality is not linear with improving business performance and the development of the UMKM business itself. Even though it has contributed greatly, its performance and development still cannot compete with MSMEs in other Asian countries. This phenomenon encourages a study to empirically model determinant factors that influence the development of MSME businesses. The result is an empirical model of business development that is explained by business performance, entrepreneurial competence, personal factors, organizational factors and environmental factors. To meet the data needs of these variables, interviews were conducted using a questionnaire. Testing empirical models and hypotheses through the research data obtained was carried out using the Structural Equation Modeling (SEM) approach. The findings from the test results are that business development is explained by business performance. While business performance is determined by entrepreneurial competence, personal factors and environmental factors. Organizational factors cannot be proven in this study.